2009
DOI: 10.21143/jhp.vol39.no1.200
|View full text |Cite
|
Sign up to set email alerts
|

Kebijakan Reklamasi Pantai Dan Laut: Implikasi Terhadap Hak Masyarakat Pesisir Dan Upaya Perlindungannya

Abstract: AbstrakThe purpose of this research is to know of the implication of coastal and seareclamation towards coastal peaple and to know the available efforts ofprotection as well as protection that should be pel/ormed. By benefitingprimary legal materials such as legislation regulations and internationalconventions as well as secondary legal materials such as text books, courtdecisions, experts' opinion, research results, journals, internet sources andnon-legal materials, it can be concluded that coastal and sea re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Dengan demikian sumber daya alam memiliki peran ganda, yaitu sebagai modal pertumbuhan ekonomi (resource based economy) dan sekaligus sebagai penopang sistem kehidupan (life support system) manusia. (Kalalo, 2009:106)…”
Section: Perlindungan Hukumunclassified
“…Dengan demikian sumber daya alam memiliki peran ganda, yaitu sebagai modal pertumbuhan ekonomi (resource based economy) dan sekaligus sebagai penopang sistem kehidupan (life support system) manusia. (Kalalo, 2009:106)…”
Section: Perlindungan Hukumunclassified
“…The retail and property industries developed along with the economic growth of the city, the impact The government, therefore, planned land reclamation of the coastal areas. The reclamation policy was in accordance with the concept of the "Waterfront City", which was the planning concept for Manado (Kalalo, 2009). also have the potential to increase pressure on biodiversity, natural resources and natural ecosystems (Widodo, 2005), which might lead to land subsidence (Soedarsono and Marfai, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Another result indicates that there is a very significant change against coastal community life pattern, mainly to non-fisher community [3]. Moreover, it is found that the coastal development in Manado Bay, Indonesia causes fishers not only as the subject of development in their demographic region [4]. This is also supported by statistic data showing that the poor in the coastal area of Manado City is assigned into categories of very poor (10 %), poor (28 %), and almost poor (62 %) [5].…”
Section: Introductionmentioning
confidence: 99%